Efektivitas Mediasi dalam Penyelesaian Sengketa Konsumen sebagai Alternatif Litigasi di Perbankan Syariah - Dava Fransisco; Damar Alfariq; Stevanny Putri Fahlevi (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
Disputes between customers and Islamic banks frequently arise, whether due to negligence, differing interpretations of contracts, or employee fraud. Litigation through the courts is often viewed as slo w, expensive, and potentially damaging to the relationship between the bank and its customers. Therefore, mediation, as part of Alternative Dispute Resolution (ADR), offers a faster, more efficient solution that aligns with Sharia principles, which emphasize deliberation. This study aims to examine the effectiveness of mediation in resolving consumer disputes in Islamic banking, from a normative and practical perspective. The method used is normative legal research with a statutory and conceptual approach. The analysis shows that mediation is more effective than litigation in maintaining customer trust, reducing dispute resolution costs, and aligning with the principles of justice and Sharia principles. However, the effectiveness of mediation is still hampered by low public understanding, limited availability of certified mediators, and weak supervision.